EFFECT OF P₂O₅ AND V₂O₅ ON THE THERMAL STABILITY OF Li₂O·2SiO₂ GLASSES - K. Moricova; P. Simon; Janik R.; Kraxner J.; Pagacova J. (Ceramics-Silikáty, 2023)

(untitled)
The evaluation of the thermal stability of lithium silicate glasses containing P₂O₅ and V₂O₅ against the crystallisation criteria based on the characteristic temperatures, activation energy values, and the length of the crystallisation induction period was conducted. Five glasses having the composition of Li₂O·2SiO₂, Li₂O·2SiO₂·0.05P₂O₅, Li₂O·2SiO₂·0.1P₂O₅, Li₂O·2SiO₂·0.05V₂O₅ Li₂O·2SiO₂·0.1V₂O₅ were prepared and the validity of the criterion was tested by applying it to the glasses. It was found that the thermal stability of oxide glasses decreases with an increasing P₂O₅ and V₂O₅ content, where the essential system of Li₂O·2SiO₂ proved to be the most stable.